Development of Prezi Media Based on Problem-Based Learning (PBL) Model in Natural and Social Science Subjects in Class IV Elementary School - Pratama, Arga; Setyasto, Novi (Jurnal Penelitian Pendidikan IPA, 2024)
The basic problem in the subjects of Natural and Social Sciences is the element of social understanding, namely the use of learning media and the planning and application of learning models that are not optimal, so student learning outcomes are not good. The purpose of this research is to develop Prezi media based on the Problem-Based Learning (PBL) model in the subject of Natural and Social Sciences in class IV of elementary school. Research and Development (R&D) with the Borg and Gall model is the type of this research. The tests used are t test and N-Gain test. The results of media validation by media experts and material experts amounted to 91.25% and 88.90% with a very feasible category. The significance value shows 0.00 and the N-Gain score obtained is 0.44 so it can be said that the increase in student learning outcomes classified as moderate. This study concludes that Prezi media based on the Problem-Based Learning (PBL) model in Natural and Social Sciences subjects in class IV elementary school is very feasible and can improve student learning outcomes.